Heading For The Peak - Suday Star, Karen Champman and Simrit Kaur (2008)
Although there have been other ratings and rankings exercises, the one that really mattered was the accelerated programme for excellence (APEX). The country's four research universities were the frontrunners and it was no surprise when all four made the short list. however, Universiti Sains Malaysia (USM) was sole institution selected.